2017
DOI: 10.1108/jocm-08-2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Procedural justice as a moderator of the relationship between organizational change intensity and commitment to organizational change

Abstract: Purpose The purpose of this paper is to investigate how and why different forms of organizational change have different levels of organizational intensity, which in turn differentiate its impact on commitment to organizational change (COC). Its purpose is to also identify how procedural justice can reduce change-related stress and buffer the strain inducing effects of job demands. Design/methodology/approach The authors tested the hypotheses using data collected from two sources in Korea. First, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 71 publications
(122 reference statements)
1
23
0
5
Order By: Relevance
“…According to Herscovitch and Meyer [43], there are three types of commitment to change: affective commitment, which supports organizational change based on trust and attachment to the organization; normative commitment, in which support to organizational change is considered a duty that arises from a sense of moral obligation; and continuance commitment, which is based on the fear of cost of resistance to change or failure to support it. According to previous research, commitment to organizational change can be viewed as a key element in promoting true change behavior of employees in the process of organizational change [5,7,44]. Thus, commitment to organizational change is essential for its successful implementation.…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
See 1 more Smart Citation
“…According to Herscovitch and Meyer [43], there are three types of commitment to change: affective commitment, which supports organizational change based on trust and attachment to the organization; normative commitment, in which support to organizational change is considered a duty that arises from a sense of moral obligation; and continuance commitment, which is based on the fear of cost of resistance to change or failure to support it. According to previous research, commitment to organizational change can be viewed as a key element in promoting true change behavior of employees in the process of organizational change [5,7,44]. Thus, commitment to organizational change is essential for its successful implementation.…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
“…Meanwhile, commitment to organizational change is a key factor in gaining the support of employees in the process of organizational change [7]. If organizational change is a success, it is important that employees do not have negative perceptions about it.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Park ( 2017 ) stated that procedural justice positively influences employee's work engagement, knowledge sharing and innovative work behavior. Lee et al ( 2017 ) showed that procedural justice can facilitates employees to accept the change of values and objectives of organization and also adapt themselves to pressures of external change. Furthermore, certain findings suggested that the process of allocating rewards is more important than the result (Lind and Tyler, 1988 ; Cohen-Charash and Spector, 2001 ).…”
Section: The Theoretical Background and Hypothesismentioning
confidence: 99%
“…Fugate et al 2012). Viele MitarbeiterInnen empfinden geplante Veränderungen als Stressoren (Lee et al 2017) und begegnen dieser Gefährdung des Status quo deshalb mit Unbehagen oder gar psychosomatischen Beschwerden (Schumacher et al 2016). Solche Diskrepanzen zwischen Ist-und Soll-Zustand, also z.…”
Section: Von Der Hemmung Zur Annäherungunclassified
“…Im Kontext von organisationalem Wandel zeigten Coch und French (1948), dass Mitarbeiter, die in die Gestaltung von Veränderungsmaßnahmen miteinbezogen wurden, seltener kündigten, bessere Arbeitsleistung zeigten und sich gegenüber Vorgesetzten positiver verhielten, als Mitarbeiter, denen die Veränderung als bereits entschieden kommuniziert wurde. Spätere Studien zeigten, dass die Wahrnehmung prozeduraler Gerechtigkeit in starkem Zusammenhang mit Annäherungsmotivation steht (Murphy und Tyler 2008), und dass das Commitment von Mitarbeitern in Veränderungsprozessen von prozeduraler Gerechtigkeit beeinflusst wird (Lee et al 2017).…”
Section: Prozedurale Gerechtigkeitunclassified